Study of the effectiveness of adjuvante treatment with the use of Carnoy’s solution: Literature review (Research, Society and Development, 2022)
Odontogenic cysts and tumors establish an important chapter of oral pathology that needs a careful evaluation in order to obtain a highly effective treatment. Due to the great potential for relapses, adjuvant therapies are essential in surgical treatment, including Carnoy's solution as an alternative. The purpose of this work is to present the use of Carnoy's Solution as a supporting treatment, in order to analyze its potential in the face of relapses. Treatments with Carnoy's solution have shown lower numbers of injury recurrence rates, however, it has considerable disadvantages ranging from devitalized bone margin to paresthesia. In view of this perspective, the use of Carnoy's solution when used correctly presents a decrease in significant recurrences. However, it was found that other adjuvant treatments without the use of Carnoy's solution presented the same results as those used, as well as a lack of research aimed at contributing to future surgical treatments from exact times of application to the number of studies provided.